AFMP2 Encodes a Novel Immunogenic Protein of the Antigenic Mannoprotein Superfamily in Aspergillus fumigatus - Chong, Ken T. K. (American Society for Microbiology, 2004)
We cloned the Aspergillus fumigatus mannoprotein 2 (AFMP2) gene, which encodes a novel immunogenic protein (Afmp2p) of the antigenic mannoprotein superfamily, in A. fumigatus. Sequence analysis revealed that Afmp2p has 510 amino acid residues, with a predicted molecular mass of 51.5 kDa. Afmp2p has a putative N-terminal signal peptide, a putative C-terminal glycosylphosphatidylinositol membrane attachment signal sequence, and an upstream GAA cleavage site commonly used for cytoplasmic membrane attachment and implicated in fungal cell wall assembly. Upstream of the GAA cleavage site, Afmp2p contains a 302-amino-acid serine- and threonine-rich region as a site for potential O-glycosylation. Within this serine- and threonine-rich region, 13 repeats of ETSTPCE(T)(n) were observed. Western blot analysis of Afmp2p in A. fumigatus fungal cell lysate and culture supernatant and immunogold staining and electron microscopy showed that Afmp2p is predominantly secreted into the culture supernatant, whereas only minimal amounts can be detected in the cell lysate and cell wall. Finally, it was observed that patients with aspergilloma and invasive aspergillosis due to A. fumigatus develop a specific antibody response against recombinant Afmp2p. The abundance of Afmp2p in secreted form, its minimal cross-reactivity with Afmp1p, and the presence of an antibody response against Afmp2p in patients with A. fumigatus infections suggest that Afmp2p is a good candidate for complementing Afmp1p in serodiagnosis of A. fumigatus infections.